2008
DOI: 10.1124/dmd.107.018747
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Drug-Metabolizing Enzymes and Transporters in Infection, Inflammation, and Cancer

Abstract: ABSTRACT:This article is a report on a symposium sponsored by the American Society for Pharmacology and Experimental Therapeutics and held at the Experimental Biology 07 meeting in Washington, DC. The presentations discussed the phenomenology, clinical consequences, and underlying mechanisms of cytochrome P450 and drug transporter regulation by inflammatory and infectious stimuli. Although considerable insights into the links between inflammatory mediators and altered hepatic drug clearance pathways have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
158
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(164 citation statements)
references
References 57 publications
4
158
0
2
Order By: Relevance
“…This has been linked to changes in liver expression of drug-metabolizing enzymes, such as cytochromes P450 (59) and more recently to that of drug transporters (60). In this sense, it has been suggested that proinflammatory cytokines, such as IL-1␀, TNF␣, and IL-6, may contribute to altered expression of hepatic drug transporters occurring during inflammation (61).…”
Section: Discussionmentioning
confidence: 99%
“…This has been linked to changes in liver expression of drug-metabolizing enzymes, such as cytochromes P450 (59) and more recently to that of drug transporters (60). In this sense, it has been suggested that proinflammatory cytokines, such as IL-1␀, TNF␣, and IL-6, may contribute to altered expression of hepatic drug transporters occurring during inflammation (61).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] CYP2E1 overexpression in cancer is attributed to the inflammatory conditions present in the tumor microenvironment characterised by increased inflammatory cytokine production which affects CYP2E1 gene expression. [18][19][20] Several CYP2E1 dependent mechanisms contributing to tumorigenesis have been suggested including formation of toxic intermediate derivatives and activated carcinogens. [21][22][23] CYP2E1 mediated ROS generation could also contribute to tumor development through pathways in which ROS play vital role such as DNA damage, enhanced angiogenic responses [24] autophagy [4,25,26] ER stress [27] and unfolded protein response (UPR).…”
Section: Introductionmentioning
confidence: 99%
“…2) This particular incident was probably owing to the decreased theophylline clearance by hepatic CYP enzymes in children infected with influenza, 3) caused by the influenza-infection-related downregulation of CYP gene expression. This incident alerted clinicians to the potential for adverse effects of an otherwise beneficial medicine in patients suffering from another disease.…”
mentioning
confidence: 99%